Preliminary Study of the Vertical Axis Wind Turbine (VAWT) Prototype at Urban Area - Irwanto Zarma Putra; Fauzun Atabiq; Didi Istardi; Ridwan Ridwan; Arif Febriansyah Juwito; Muhammad Agil Wildan; Muhammad Ridlo Alfianto; Rahman Hakim (Politeknik Negeri Batam, 2021)
This research complements the shortcomings of PLTB, namely by adding a Monitoring System to the Wind Power Plant at Batam State Polytechnic. By addition of sensors, installations, and a control panel containing instruments for monitoring wind conditions, Savonius turbine rpm, and pico-generator output electrical characteristics. The method used is conventional, starting from mechanical design, program development, and installation to testing. This study's preliminary results indicate that wind at the PLTB Polibatam location is not continuous. It does not occur, even though the maximum wind speed can reach 8.9 m / s. The implementation of the savonius-type wind turbine in this study can generate electricity around 87.83 kW / week or about 0.61 kW / hour.